MUSICAL ABILITIES OF STUDENTS IN THE CONTEXT OF THE PROBLEM OF VOCAL AND CHORAL SKILLS FORMATION - Gopkalo, T.P. (Pedagogy of Higher and Secondary Education, 2010)
This article is reflected the describes components of musical abilities of pupils that affect the quality of forming vocal-chorus abilities, within components musical Unities. discusses such a notion as "musical ear", "feeling rhythm", musical memory", examines the shortcomings of the musical ear.